Surface tension models for a multi-material ALE code with AMR. (27th June 2017) - Liu, Wangyi; Koniges, Alice; Gott, Kevin; Eder, David; Barnard, John; Friedman, Alex; Masters, Nathan; Fisher, Aaron
Highlights: Surface tension models implemented in 3D multi-physics multi-material code ALE–AMR. Diffuse-interface Kortewge-type surface tension model is shown to produce droplets. Height function and volume-fraction interface reconstruction is optimum for EUV app. Adding surface tension effects results in only a modest increase in computing cost. Surface tension can impact droplet dynamics relevant to EUV lithography sources. Abstract: A number of surface tension models have been implemented in a 3D multi-physics multi-material code, ALE–AMR, which combines Arbitrary Lagrangian Eulerian (ALE) hydrodynamics with Adaptive Mesh Refinement (AMR). ALE–AMR is unique in its ability to model hot radiating plasmas, cold fragmenting solids, and most recently, the deformation of molten material. The surface tension models implemented include a diffuse interface approach with special numerical techniques to remove parasitic flow and a height function approach in conjunction with a volume-fraction interface reconstruction package. These surface tension models are benchmarked with a variety of test problems. Based on the results, the height function approach using volume fractions was chosen to simulate droplet dynamics associated with extreme ultraviolet (EUV) lithography.